Examining the Effect of Social Media Engagement on Purchase Intention: A Study of Generation Z Consumers - Wikrama Wardana (Dinasti International Journal of Education Management And Social Science, 2025)
The digital revolution has significantly changed the marketing landscape, particularly through social media, which is now the main platform for building relationships between brands and consumers. This study aims to examine the influence of social media involvement on the purchase intention of Generation Z consumers in Indonesia. This study uses a quantitative approach with a survey method, collecting data from 250 Generation Z respondents who actively interact with brands on social media. Data analysis was carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that social media engagement has a positive and significant effect on purchase intent, with a strong path coefficient and a high level of significance. These findings reinforce the Stimulus-Organism-Response (S-O-R) model in the context of digital consumer behavior, as well as emphasize the importance of active engagement strategies to drive purchasing decisions. This research makes a theoretical contribution to the social media engagement literature and offers managerial implications for brands looking to optimize digital interactions with Generation Z consumers.